Efektivitas Model Pembelajaran Contextual Teaching And Learning Dalam Meningkatkan Hasil Belajar Sejarah - Isbandiyah Isbandiyah; Sarkowi Sarkowi; Rohana Rohana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research aims to analyze effect of the Contextual Teaching and Learning model on history learning outcomes at SMK Negeri 1 Lubuklinggau and analyze effectiveness of the Contextual Teaching and Learning model in improving history learning outcomes at SMK Negeri 1 Lubuklinggau. The type of research is a pure experimental research with used pretest-postest group design. The sample the students at X AKL3 as the experimental class with the students X X AKL1 as the control class. The result of data analysis in this research concluded that: (1) Contextual Teaching and Learning model affect the history learning outcomes at SMK Negeri 1 Lubuklinggau; and (2) Contextual Teaching and Learning model are affective in improving the history learning outcomes at SMK Negeri 1 Lubuklinggau. Keywords: history learning outcomes, Contextual Teaching and Learning model (CTL)